Gymnopilus penetrans and G. swaticus sp. nov. (Agaricomycota: Hymenogastraceae); a new record and a new species from northwest Pakistan - Khan, Junaid; Kiran, Munazza; Jabeen, Sana; Sher, Hassan; Khalid, Abdul Nasir (Phytotaxa, 2017)
Two Gymnopilus species are described and illustrated from northern parts of Khyber Pakhtunkhwa province, Pakistan. Gymnopilus swaticus is described as new to science based on morphological characters and data from nITS and nLSU. Gymnopilus penetrans is a new record for Pakistani mycobiota.